PENGARUH MOTIVASI, KOMPETENSI, KOMPENSASI DAN KINERJA KARYAWAN DI PT ANGLER BIOCHEMLAB SURABAYA - jurnalpps pps; Atha Fitriani; Mei Indrawati; Hidayat ÔÇÄ (Jurnal Manajerial Bisnis, 2019)
The purpose ofthis research is to investigate and analyze the effect of Work Motivation, Competence, and Compensation affecting/giving impact on employee performance in PT Angler Biochemlab Surabaya. To analyze the effect of the independent variables (Work Motivation, Competence, and Compensation) on the dependent variable (performance), we use multiple regression analysis to know the most influential variables. The population is 124 people, using simple random technique (Simple Random Sampling), then take 91 samples. The Sampling that is used is Krecjie table. The results of this study illustrate that all the variables affect the employee performance. The results of simultaneous research all independent variables have significant effect on the dependent variable. Partially every variable of work motivation, competence and compensation have a positive effect on employee performance. And of the three independent variables are the most dominant effect on employee performance is a variable work motivation. This research could become a refernce for all parties to enhance the officialsÔÇÖ performances. Thus, there is a need of attention towards the motivation works valid within the organization. Conversely, there is a need to continuously conduct the officialsÔÇÖ development throught the Competation and Compensation activities the officials.